Linking Identity Leadership and Team Performance: The Role of Group-Based Pride and Leader Political Skill - Hou, Liang; Song, Lynda Jiwen; Zheng, Guoyang; Lyu, Bei (Frontiers in Psychology, 2021)
Recent trends in the leadership literature have promoted a social identity approach of leadership that views leadership as the process of representing, advancing, creating, and embedding a sense of shared identity within a group. However, few empirical studies explore how and when global identity leadership affects team performance at the workplace. To address this lacuna, we used multi-source and two-wave data among 81 teams to explore the role of group-based pride and leader political skill in the association between identity leadership and team performance. Results suggest that identity leadership positively predicts team performance through the mediating role of group-based pride. Furthermore, leader political skill moderates the indirect effect of group-based pride, such that the indirect effect is stronger when leader political skill is high rather than low. Finally, several theoretical and practical implications of this study are discussed, and future research directions are also suggested.